Reynolda Gardens in the spring, 1963. - (:unkn) unknown (Forsyth County Public Library)
WSJ 3-23-63 p.1.
Reynolda Gardens in the spring, 1963.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth